West Indies island of Cuba - United States Naval surveys (Washington, D.C. : U.S. Navy Hydrographic Office, 1957)
Diagram represents a well detailed map of the island of Cuba and the soundings in fathom.
Level 1 deterioration.
Special Collections Floor.
Keywords: Cartographic material; Cuba; Maps